2008
DOI: 10.1299/jee.3.286
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Flame Characteristics of Jet Diffusion Flames in Cylindrical Furnaces (2nd Report, Scaling of EINOx)

Abstract: The flame characteristics of confined flames are investigated for propane and hydrogen jet nonpremixed flames in cylindrical furnaces. The flame characteristics can be strongly dominated by the combination of the burner and furnace geometries. In the present study, the effects of the inner diameter of the cylindrical furnace D 1 , the turbulence at the flame boundary, and the global equivalence ratio φ are examined in terms of the emission of NOx. The emission index of NOx, EINOx, decreases roughly with these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…With regard to the relationship between NOx emissions and the recirculated burned gas, Noda and co-workers (Noda et al, 2007, Nada et al, 2008 investigated the effect of dilution resulting from burned gas recirculation on NOx emissions from laboratory-scale cylindrical furnaces with different diameters and found that a large furnace diameter enhances the extent of dilution. Noda's result suggests another cause for the reverse trend seen in the present study, in terms of the cross-sectional furnace size.…”
Section: And 6) This Difference Between Einox Valuesmentioning
confidence: 99%
“…With regard to the relationship between NOx emissions and the recirculated burned gas, Noda and co-workers (Noda et al, 2007, Nada et al, 2008 investigated the effect of dilution resulting from burned gas recirculation on NOx emissions from laboratory-scale cylindrical furnaces with different diameters and found that a large furnace diameter enhances the extent of dilution. Noda's result suggests another cause for the reverse trend seen in the present study, in terms of the cross-sectional furnace size.…”
Section: And 6) This Difference Between Einox Valuesmentioning
confidence: 99%